EFEKTIVITAS PROGRAM ARABIC CAMP DALAM MENUNJANG PENGUASAAN MAHARAH KALAM - Syagif, Ahmad; Nurhidayati, Titik (Fitrah, 2023)
This research aims to identify the extent of the effectiveness of the Arabic camp program in supporting the mastery of maharah kalam. This research uses an experimental design and applies a pre-experimental method with a one group pretest and posttest design with three steps: 1) Pre-test carried out to determine variables, 2) Give X treatment to the subject, 3) Carry out post-test, and analyze scores pre-test and post-test to determine the differences caused by the treatment. The population of this study was 200 MTSN 1 Bima City students consisting of 6 classes. Then the researchers determined a sample of 20 people using purposive sampling technique. The results of data analysis show that student learning achievement in the pre-test was 71.7 and post-test was 86.1. This shows that Arabic camp is a good strategy to support the mastery of maharah kalam in MTSN 1 Kota Bima students. After analyzing the data using the t test formula, the t test value (11.86) was greater than the t table value (2.093). There is a significant influence of the Arabic language camp program on student achievement in the Arabic language learning process. The implementation of the Arabic camp at MTSN 1 Bima City lasted for three days and this had a positive effect on students' skills in maharah kalam.